Enzymes involved in ROS scavenging in nodules of Datisca glomerata and Ceanothus thyrsiflorus. - Marco Guedes Salgado (Stockholm University, 2018)
The nodules transcriptomes of Datisca glomerata and Ceanothus thyrsiflorus were de novo assembled by Trinity and annotated using the Trinotate pipeline. Transcript abundance was estimated for enzymes involved in ROS detoxification by RSEM and presented as transcript per million reads (TPM).
Keywords: 60705 Plant Physiology; Computational Biology; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)